Application of whole exome sequencing in patients with primary ciliary dyskinesia - Ke CHEN; Jing SHI; Lijuan HU; Li ZHANG; Minlu CAO; Wei GUO; Meiling JIN (Zhongguo Linchuang Yixue)
A 29-year-old man visited Zhongshan Hospital, Fudan University in December 2021. The patient presented with recurrent coughing, sputum, and wheezing, high level of serum total IgE, positive aspergillus fumigatus-specific IgE and extremely severe mixed ventilatory dysfunction. These features and thoracic CT results scan showed bronchiectasis and allergic bronchopulmonary aspergillosis. In consideration of his clinical characteristics, including low levels of fractional exhaled nitric oxide (FeNO), and nasal nitric oxide (nNO), persistent cough after birth, consanguineous marriage of his parents, etc. we ratiocinated a possibility of hereditary diseases, especially primary ciliary dyskinesia (PCD). From this perspective, whole exome sequencing (WES) was performed and the diagnosis of PCD was ultimately confirmed.